Evaluation of Growth and Sap Quality of Five Sorghum Varieties (Sorghum bicolor L. Moench) at the Primordial Stage in Dryland - Fajar Rochman; Priyadi; Rizky Rahmadi (JURNAL AGRIMENT, 2025)
Sorghum is a vital crop for food and bioenergy, especially in drylands. This study aimed to evaluate the growth and sap production of five sorghum varieties, namely Super 2, Mandau, Bioguma, Super 1, and Suri 4, cultivated in dryland. The experiment was conducted using a Randomized Block Design with five replications. Parameters were measured at the primordial stage, including plant height, leaf count, stem diameter, wet stover weight, stem weight, sap volume, and Brix percentage. Data were analyzed using ANOVA and tested with the 5% LSD test. The results showed significant differences in plant height, wet stover weight, stem weight, and Brix percentage. Super 1 variety showed the highest performance in plant height at 243.62 cm, wet stover weight at 1029.50 g, and stem weight at 624.00 g. Conversely, the Mandau variety, which was the shortest at 131.50 cm, produced the significantly highest Brix content of 7.02%. There were no significant differences observed in leaf count, stem diameter, or sap volume among the varieties. This suggests Super 1 is superior for biomass production, while Mandau shows the best potential for sugar content at the primordial stage in dryland conditions.